Heterotic grouping of tropical maize inbred lines and their hybrid performance under stem borer infestation and low soil nitrogen condition in west and central Africa - Olayiwola, M.O.; Ajala, S.; Ariyo, O.J.; Ojo, D.K.; Gedil, Melaku A (Springer, 2021)
Low soil nitrogen (low-N) and stem borer attack are two of the major stresses limiting maize production in West and Central Africa (WCA). Thus, there is need to intensify efforts aimed at identifying inbred lines with resistance and tolerance to these stresses for hybrid development. The objectives of the study were to determine the combining ability of maize inbred lines, classify them into heterotic groups using both conventional and marker-based approaches, compare the efficiency of the different grouping methods and evaluate the performance of the hybrids generated from the inbred lines under contrasting environments. Ten white maize inbred lines with varying levels of resistance to stem borers were selected and crossed in a diallel in 2015. The resulting 45 hybrids were evaluated together with five checks in 10 environments under low-N, artificial stem borer infestation and non-stress conditions in Nigeria. General combining ability (GCA) and specific combining ability (SCA) were highly significant (p ≤ 0.01) for most of the traits studied but GCA was predominant over SCA under each and across research conditions. Inbred line 2 combined significant positive GCA for grain yield with significant negative GCA for traits of resistance to stem borers and tolerance to low-N. Each of the grouping methods classified the inbred lines into 3 heterotic groups but SCA and heterotic groups’ specific and general combining ability had the joint highest breeding efficiency. Hybrids 1 × 4, 2 × 3, 1 × 6 and 2 × 5 were identified to be high yielding and stable across environments and can serve as candidates for further on-farm evaluations and eventual release in WCA.